Kemampuan Aparat Pelaksana Program Pelatihan Tata boga Pada Dinas Tenaga Kerja Kota Manado - MANIKOME, NOVATY; LIANDO, DAUD MARKUS; MAMENTU, MICHAEL (Sam Ratulangi University, 2018)
The city of Manado is one of the emerging cities in the province of North Sulawesi and one of theimportant tasks of the government in supporting regional development is the handling of unemploymentcurrently faced. One of the programs run by the Manado City Labour Office is a training program forthe Tata boga, this program aims to help housewives who do not have jobs that have the opportunity toopen their own business in order to increase the income of their family. Therefore, this study aims toanalyze the capability of the implementing officers of the Tata boga training program at the Departmentof Labor.To analyze the data using the capability theory approach from Hersey and Blanchard (2006: 20)covering 1) technical skill; 2) social skills (social skills); 3) conceptual skills (conceptual skills).The results of this study and discussion found that the basic skills of the executing apparatus arenot optimal, the ability of the technique is good enough, the social ability is also very good, but theconceptual ability is still low due to lack of conceptual mastery of an organization from theimplementation of the program Tata boga so monitoring of the participants Tata boga training is notdone thoroughly but only some participants. From this research can be drawn the conclusion that theability of officers of training program Tata boga program at the Manado city Labour Office has notbeen maximized due to: the absence of monitoring or monitoring of the implementing officers of allparticipants who attended the Tata boga program training but only part of the monitored the groupparticipants Tata boga formed during the training so it cannot be seen how many who develop and donot develop knowledge and assistance obtained from the Manado City Labour Office.Keywords: Ability, apparatus, training